“Comparación de las complicaciones del levonorgestrel y la combinación norgestrel atinilestradiol – Hospital Banda de Shilcayo período 1996 – 1997” - Arce Saavedra, Segundo N. (1997)
This research traba._io is a study of scriptivo, is also comparative with prospective data and so it was long! tudinal in time, which is an applied research, which was developed in the hospital, rural of the Banda de Shilcayo during the period from 1996 to 1997, to ·comparar applications of levonorgestrel and the combinacu:'. m Norgestrel - Etinilestracuol and este\blecer an alternative change in study population if these complications are minor and controlablet3 in the control group. As 70 women discussed who the implantation of levonorgestrel and equal number of mu ~ 1eres used il Norgeatrel-ethinyl estradiol with their respective controls. The complications of both hormonal contraceptives than significance ee:t t.uvieron ~: \distica are: menstrual changes in levonorge, stral (61.42 '. t ~) and norgestrel-ethinyl estradiol (41.4:.: 1 ~ ~); dizziness in norgestrel ethinyl estradiol-levonorgestrel (62.86%); bleeding intermestrual ~ s levonorg...